2021
DOI: 10.1177/17543371211058031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of jump heights, landing techniques, and participants on vertical ground reaction force and loading rate during landing on three different Korean teeterboards

Abstract: Korean teeterboard is one of the most physically and technically demanding circus disciplines. Two performers take turns jumping vertically and land with high impact. The aims of this study were to (1) compare the stiffness across three different teeterboards, and (2) compare Peak Landing Force (PLF) and Maximal Loading Rate (MLR) of four acrobats performing jumps from three teeterboards using four landing techniques (normal, smooth, straight legs, and empty board). Pressure sensors were used to determine reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These results are similar to those collected during the SBS 90° execution mode. However, our results in the SBS 270° and the SBS 180° execution mode are higher than the above-cited works [ 17 , 27 ], but they are comparable with those of Cossin et al [ 43 ] who reported 13.5 BW in vertical ground reaction force during back tucked somersault landing on three different Korean teeterboards in acrobat gymnasts.…”
Section: Discussionsupporting
confidence: 85%
“…These results are similar to those collected during the SBS 90° execution mode. However, our results in the SBS 270° and the SBS 180° execution mode are higher than the above-cited works [ 17 , 27 ], but they are comparable with those of Cossin et al [ 43 ] who reported 13.5 BW in vertical ground reaction force during back tucked somersault landing on three different Korean teeterboards in acrobat gymnasts.…”
Section: Discussionsupporting
confidence: 85%
“…Acrobats must synchronize their take-off with their partner's landing, and a very low stiffness can hinder this synchronization. On the other hand, higher stiffness can result in uncomfortable impact forces for the acrobat [10]. Additionally, teeterboards are made of ash wood, a natural and inconsistent material, and their mechanical properties can vary from board to board, making it even more challenging to construct standardized teeterboards.…”
Section: Discussionmentioning
confidence: 99%
“…The European Federation of Professional Circus Schools (FEDEC) [9] recommends a low stiffness board for beginners because it minimizes timing errors. However, some professionals prefer higher stiffness to have more propulsion, while others prefer lower stiffness to avoid high loads [10], combined with an increased board angle. Teeterboards are typically tapered and made of ash wood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well established that landing from a jump with limited knee flexion produces a large vertical ground reaction force [ 143 , 153 ]. This high force is considered a negative by most practitioners, and techniques to reduce these peak vertical ground reaction forces are often taught [ 142 – 144 ]. However, it is unknown if the athlete is better off landing with large ground reaction forces if different strategies are used over time (e.g.…”
Section: Discussion Of Theoretical Frameworkmentioning
confidence: 99%